2008
DOI: 10.1002/pmic.200700888
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis for inhibitory effect of chitosan oligosaccharides on 3T3‐L1 adipocyte differentiation

Abstract: In the present study, we performed a differential proteomic analysis using 2-DE combined with MS to clarify the molecular mechanism for the suppressive effect of chitosan oligosaccharides (CO) during differentiation of adipocyte 3T3-L1. Cell differentiation was significantly inhibited by CO at the concentration of 4 mg/mL. Protein mapping of adipocyte homogenates by 2-DE revealed that numerous protein spots were differentially altered in response to CO treatment. Out of 50 identified proteins showing significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 79 publications
1
29
1
1
Order By: Relevance
“…CLIC1 has been shown to interacts with Sedlin. Sedlin which as a components of TRAPP complex, has been reported to be involved in a defect in cartilage transport from endoplasmic reticulum to the Golgi complex [22].CLIC1 is also involved in cell cycle regulation [23] and in the regulation of cell proliferation and differentiation [24,25]. Recently, several studies have shown that CLIC1 is highly expressed in malignant tumors, such as gastric [26], colon [27], and liver [28,29] cancers.…”
Section: Introductionmentioning
confidence: 99%
“…CLIC1 has been shown to interacts with Sedlin. Sedlin which as a components of TRAPP complex, has been reported to be involved in a defect in cartilage transport from endoplasmic reticulum to the Golgi complex [22].CLIC1 is also involved in cell cycle regulation [23] and in the regulation of cell proliferation and differentiation [24,25]. Recently, several studies have shown that CLIC1 is highly expressed in malignant tumors, such as gastric [26], colon [27], and liver [28,29] cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Adipogenesis is known to be closely related to the etiologies of obesity and obesity-related metabolic disorders (Spiegelman et al, 1993). A mouse preadipocyte cell line 3T3-L1, originally derived from a mouse embryo, can be differentiated into adipocytes, and has been widely used as an in vitro model for studying obesity (Green and Meuth, 1974;Harmon and Harp, 2001;Madsen et al, 2005;Rahman et al, 2008). During adipogenesis, 3T3-L1 cells change from fi broblast-like preadipocytes to spherical adipocytes and accumulate large fat droplets containing triglycerides (Jessen and Stevens, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of body fat arises from a chronic imbalance between energy acquisition and expenditure that may lead to a pathologic growth of adipocytes, characterized by increased fat cell size and number [5]. It is known that the amount of adipose tissue can be regulated by the inhibition of adipogenesis and fat deposition [6]. Fat deposition in adipose tissue can be reduced by reducing lipid uptake by adipocytes via suppressing lipoprotein lipase (LPL) or reducing lipid synthesis through inhibiting fatty acid synthase (FAS) among other mechanisms [7].…”
Section: Introductionmentioning
confidence: 99%